(untitled) (مجلة الرازي الطبية, 2025)
Patients with reduced kidney function are at an increased risk for complex drug-related problems due to altered drug pharmacokinetics and the presence of multiple comorbidities. This study aimed to identify and evaluate drug-related problems (DRPs) in this vulnerable patient population to enhance pharmacotherapy management. A retrospective analysis was performed on a cohort of 60 patients with reduced kidney function. Demographic and clinical data, including age, gender, and the number of comorbidities, were collected. Medication-related issues were categorized and quantified, focusing on unnecessary drug therapy, dosage concerns, the need for additional therapy, ineffective drugs, adverse drug reactions (ADRs), and drug-drug interactions (DDIs). In this study, a total of 60 patients with low kidney function were evaluated, whose average age was 63 ± 2.39 years. The most frequently represented age groups were 60–69 and 70–79 years (each 13 patients), followed by the 80–89-year-old group (10 patients). The study consisted of 23 males (38.3%) and 37 females (61.7%), with an average of 3.4 Comorbidities per patient. A detailed analysis of the drug-related issues was conducted, in which several notable conclusions were detected. First, unnecessary drug therapy was identified in five cases (4.35%). Secondly, dosage-related issues were important, with 23 examples where the dose was too high (20%) and 10 examples where the dosage was very low (8.70%). Third, an additional drug therapy requirement was noted in 26 cases (22.61%). Finally, ineffective drugs were identified in 12 cases (10.43%). 16 examples (13.91%) reported adverse drug reactions (ADRs), while drug-drug interactions (DDIs) were seen in 23 examples, accounting for 20% of the total incidents. The study emphasizes considerable proliferation of drug complications among patients with low renal function, mainly due to dosage-related issues and the need for additional medications. Conclusions emphasize the importance of individual and careful drug management in this demographic, which aims to reduce deformed results and to improve medical efficacy.